Let's simplify step-by-step.
−3x2−5x2(4x3−x2)(2)
Distribute:
=−3x2+−40x5+10x4
Answer:
=−40x5+10x4−3x2
Step-by-step explanation:
first you have to take all similar variable on the same side of the equation and the constants on the other side then solve the question .
example : -12x + 9 = -15x
-12x +15x = -9
3 x = -3
X = -3/3= -1
x = -1
like this you can solve all the other equation ..
<em>Hope </em><em>this </em><em>will </em><em>be</em><em> helpful</em><em> to</em><em> you</em><em> </em><em>.</em><em>.</em>
<em>plz </em><em>mark</em><em> my</em><em> answer</em><em> as</em><em> brainlist</em><em> </em><em>if </em><em>you</em><em> </em><em>find </em><em>it </em><em>useful</em><em>.</em><em>.</em>
Answer:
C. y=3x-6
Step-by-step explanation:
The answer for this question is 8/1
Answer:
13.5 and 13.5
Step-by-step explanation: